1991
DOI: 10.1029/90jb02743
|View full text |Cite
|
Sign up to set email alerts
|

Convection in three dimensions with surface plates: Generation of toroidal flow

Abstract: This work presents numerical calculations of mantle convection that incorporate some of the basic observational constraints imposed by plate tectonics. The model is three‐dimensional and includes surface plates; it allows plate velocity to change dynamically according to the forces which result from convection. We show that plates are an effective means of introducing a toroidal component into the flow field. After initial transients the plate motion is nearly parallel to transform faults and in the direction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
139
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(142 citation statements)
references
References 44 publications
3
139
0
Order By: Relevance
“…Oceanic plate velocities are time-dependent and are dynamically determined using the total integrated shear stresses at the base of each plate (a force-balance calculation). This method of modeling plates and determining their velocities [Gable et al, 1991] has been shown to yield plate velocities and mean heat flux values in agreement with modeling methods that utilize rheologically defined plates [Koglin et al, 2005].…”
Section: Model Descriptionmentioning
confidence: 68%
See 1 more Smart Citation
“…Oceanic plate velocities are time-dependent and are dynamically determined using the total integrated shear stresses at the base of each plate (a force-balance calculation). This method of modeling plates and determining their velocities [Gable et al, 1991] has been shown to yield plate velocities and mean heat flux values in agreement with modeling methods that utilize rheologically defined plates [Koglin et al, 2005].…”
Section: Model Descriptionmentioning
confidence: 68%
“…[6] We model mantle convection using the hybrid finitedifference spectral-method code MC3D [Gable et al, 1991] to solve the equations for mass, momentum and energy conservation and use the extended Boussinesq approximation to include a depth-dependent mantle viscosity characterized by a factor of 36 increase from the upper mantle to the lower mantle.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Calculations were done using the Cartesian numerical code first written by Gable [1989] and Gable et al [1991] and later modified by Ito et al [ 1996] to incorporate variable viscosity. The numerical setup is illustrated in Figure 1.…”
Section: Governing Equations and Numerical Methodsmentioning
confidence: 99%
“…Hager and O'Connell [1981] and Bunge and Richards [1996] imposed the velocity field at the surface. As opposed to this, Gable et al [1991] and Monnereau and Quéré [2001] prescribed only the initial plate geometry and introduced a coupling between plates and bulk convection supposing no direct interaction between the plates. There is a certain free space between the plates to allow an evolution of the plates.…”
Section: Plate-like Motions Of the Lithospherementioning
confidence: 99%